Interactive Hadith Application Review for Islamic Education - Supi Siti Solihah (Nusantara Journal of Multidisciplinary Science, 2025)
Islamic education is one of the important aspects in the formation of the character of the young generation. In today's digital era, technology can be an effective tool to enrich the learning process, one of which is through interactive hadith applications. Interactive hadith applications are designed to make it easier for students to understand and memorize the hadiths of the Prophet Muhammad SAW in a more interesting and interactive way. This study aims to review interactive hadith applications that can be used in Islamic education, focusing on aspects of functionality, interactivity, and effectiveness in helping users learn and memorize hadith. In this study, the method used is a literature review of various interactive hadith applications available on the Android and iOS platforms. These applications are assessed based on ease of use, interactive features such as audio, text, and additional explanations that enrich the context of the hadith. The results of the study indicate that these applications have great potential in improving understanding and memorization of hadith, but also have deficiencies in terms of depth of explanation and features that still need to be improved. This study is expected to contribute to the development of more effective and interesting Islamic education applications, especially for students in educational institutions such as MDTA AQWAUL YAQIEN